Influence Of Parenting Style On The Developmentof Adolescentpersonality Reflected In J.K Rowling's The Casual Vacancy (2012): A Behaviourist Approach - Pratiwi, Ariyani, Dr. M. Thoyibi, M.S (2017)
This study will focus on how parenting style influences the development of adolescent personality reflected on J.K. Rowling's The Casual Vacancy based on Behaviourist Approach. The aims of the study are to analyze what kind of parenting styles used by certain families in the novel and their influence on adolescent personality development. The type of this research is descriptive qualitative. The researcher uses two data sources that are primary and secondary. The primary data source of the study is The Casual Vacancy novel by J.K Rowling. The researcher gets the data from the novel includes the narration, monologue and dialogue. Secondary data are the supporting data taken from other sources like literary books, criticisms, interviews, and some articles that related to the novel on the internet. The technique of data collection are reading the data repeatedly, taking notes, underlying the important words, arranging the data, selecting the data, and drawing conclusion. The technique of data analysis is descriptive interactive which comprises three procedures, namely: data reduction, data display, and conclusion. From this research, the researcher can draw some conclusions: 1) There are three parenting styles in The Casual Vacancy novel, they are Authoritarian, Indulgent and Uninvolved Parenting Style where all parents have a difficult relationship with their children, 2) Parenting styles give significant influence on adolescent's way of walking/dressing, way of talking, way of interacting with others, way of expressing emotion, and way of life. It is very necessary for parents to observe if their parenting style is suitable for their children or not by keeping good communication with their children, because it will determine the children/ adolescent's personality development in the future.